2001
DOI: 10.1108/01437730110410107
|View full text |Cite
|
Sign up to set email alerts
|

The transformational‐transactional leadership model in practice

Abstract: Explores the nature of transformational and transactional leadership among business executives. Comments reveal that most executives believe there are weaknesses as well as strengths with both leadership constructs in practice. Overall, major leadership strengths are in the role modelling, coaching, and consideration behaviors of executives. Major weaknesses are in failure to motivate and challenge workers beyond the expected outcomes. Other facets of each of the four transformational and two transactional lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
0
14

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(127 citation statements)
references
References 17 publications
(19 reference statements)
5
108
0
14
Order By: Relevance
“…staff meetings) will be able to proactively build effective relationships and reach work goals in a collaborative fashion, through giving recognition and empathising appropriately as well as facilitating conflict within the group. This partly corroborate with previous research results of Sarros and Santora (2001).…”
Section: Building Working Relationshipssupporting
confidence: 83%
See 1 more Smart Citation
“…staff meetings) will be able to proactively build effective relationships and reach work goals in a collaborative fashion, through giving recognition and empathising appropriately as well as facilitating conflict within the group. This partly corroborate with previous research results of Sarros and Santora (2001).…”
Section: Building Working Relationshipssupporting
confidence: 83%
“…Having an understanding of the impact of individuals' emotions and the collective emotions of a team on the way they act and think, enables an individual to modify his or her own behaviour to accommodate the situation and individuals involved. Once again, this finding partially confirms research done by Sarros and Santora (2001). In their explorative study of transformational and transactional leadership they concluded that transformational leaders are able to switch from one leadership style to another to suit the individual and the situation in order to maximize results (individualized consideration).…”
Section: Gaining Commitmentsupporting
confidence: 76%
“…Hence, this study intends to fill the gaps by analyzing the relationship between leadership characteristic styles (idealize influence, motivational inspiration, individualize influence, intellectual stimulation) and succession planning (preparing for future leader and career development) in the Malaysian public sector. Sarros and Santora (2001) noted that leadership is the important function that has the capacity to organize the change in the constitution. Burn (1978) converts followers into leaders and may convert leaders into moral agents, while Murphy and Ensher (2008) mentioned leadership is one of very important needs for the success of the organization and leadership characteristic elements contribute to the leadership effectiveness.…”
Section: International Journal Of Asian Social Sciencementioning
confidence: 99%
“…Furthermore, Burns (1978) argued that transformational leaders inspire followers by aligning their own and followers value system with important moral principle. Based on these scenarios a lot of researches have been carried out on transformational leadership in organizational settings (Jamilah et al 2012;Weichun et al 2011;Bass and Avolio 1995) The result of these studies has identified effective transformational leadership style depends on how employee's perceived their leader in terms of goals settings and motivating them to achieve those goals (Jamilah et al 2012;Beamish, et al 1999;Truckenbrodt 2000;Sarros andSantora 2001 Asgari et al 2009).…”
Section: Introductionmentioning
confidence: 99%